Analysis on Fracture Failure of Mixer Top Cover - GE Wei - jing, HUANG Sheng - yin (Cailiao Baohu)
The AlSi7Mg1A Al alloy top cover of a mixer fractured in use. Metallographic microscope, Vickers hardness tester, pH value tester and SEM were used to detect and analyze the fracture reason. Results showed that the hardness, composition and metallographic structure of the top cover met the technical requirements. There was serious corrosion on the fracture surface and the crack propagated along the intergranular crystal like ice sugar. There were many chemical elements such as oxygen, aluminum and chlorine in the corrosion products. The reason for the corrosion was that the corrosion battery was formed by the slurry on the copper joint, the screw part of the top cover and the surface, which caused the stress corrosion cracking in the stress environment. Satisfactory protective performance were achieved by adopting anticorrosive measures such as changing the joint material, applying anti - corrosion coating and designing the protective shell of the top cover.